2002
DOI: 10.1002/bjs.4023
|View full text |Cite
|
Sign up to set email alerts
|

Individual inflammatory response of human blood monocytes to mesh biomaterials

Abstract: Background: Alloplastic implants such as those employed in hernia repair induce distinct local inflammation and seroma production. As monocytes take a key position in the inflammatory foreign body reaction, their specific release of cytokines was investigated in vitro after incubation with alloplastic materials.Methods: Human blood monocytes were isolated from buffy coats of 42 healthy blood donors. Cells were cultivated in polystyrene culture wells (4 × 10 6 cells/well) on polypropylene-polyglactin mesh, on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 22 publications
0
54
0
6
Order By: Relevance
“…Different factors can influence the acute inflammatory response to prosthesis implantation. Patients themselves have been identified as an independent factor in the inflammatory response of monocytes to biomaterials and have been classified as low and high responders (2). Other factors that influence the inflammatory reaction are density (10), size (11) and the physical characteristics of the prosthesis such as texture and porosity of each biomaterial (12)(13)(14).…”
mentioning
confidence: 99%
“…Different factors can influence the acute inflammatory response to prosthesis implantation. Patients themselves have been identified as an independent factor in the inflammatory response of monocytes to biomaterials and have been classified as low and high responders (2). Other factors that influence the inflammatory reaction are density (10), size (11) and the physical characteristics of the prosthesis such as texture and porosity of each biomaterial (12)(13)(14).…”
mentioning
confidence: 99%
“…Herniotomi operasyonlarında kullanılan mesh'in fiksasyonu sırasında operasyon alanından geçen sinirlerde yaralanma olabileceği gibi, mesh'in yarattığı enflamasyona karşı da sinir hasarı olabileceği belirtilmektedir. [17,18] Buna karşılık 2612 hasta üzerinde yapılan bir araştırmada mesh kullanılan hastalar ile kullanılmayan hastalar arasında kronik ağrının görülme sıklığı yönünden anlamlı bir fark bulunamamıştır.…”
Section: Discussionunclassified
“…Herni operasyonu sonrası kronik ağrı gelişen hastaların çoğunda ameliyat öncesi başağrısı, irritabl kolon sendromu veya sırt ağrısı olduğu saptanmıştır. [14][15][16][17][18][19][20][21][22] Başka bir çalışmada ameliyat öncesi dönemde ağrısı olmayan ve herni operasyonu geçiren kişilerin bir yıllık takipleri sonrası ağrı skorları ameliyat öncesi dönemde ağrısı olanlara göre belirgin derecede dü-şük çıkmıştır. [23] Çalışmamızda ameliyat öncesi ağ-rısı olanlarda kronik ağrı gelişimi insidansı %21.8 olarak bulunmuştur.…”
Section: Discussionunclassified
“…It has been shown that, in the abdominal wall, mesh retraction is related to the degree of tissue inflammation around the mesh after implantation 14 . This host reaction depends on both biocompatibility of the foreign material and the patient's immune system 15 . It is known to take place in the first few weeks but can last as long as 12 months after surgery 16 .…”
Section: Discussionmentioning
confidence: 99%